Harm reduction national and international perspectives - Inciardi, James A.; Harrison, Lana D.; Sage eBooks (Thousand Oaks, Calif. ; London : SAGE, 2000)
Harm reduction programmes accept the reality of drug use while attempting to reduce its harmful consequences to individuals and society. Here, contributors discuss the philosophical basis and history of such policies and examine their outcomes.
Specialized.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Drug abuse -- Prevention; Drug abuse -- Treatment; Drug abuse -- Prevention -- Government policy; Drug abuse -- Treatment -- Government policy; Electronic books